Angiotensin II type 1 and 2 receptors and lymphatic vessels modulate lung remodeling and fibrosis in systemic sclerosis and idiopathic pulmonary fibrosis (Clinics, 2014)
OBJECTIVE: To validate the importance of the angiotensin II receptor isotypes and the lymphatic vessels in systemic sclerosis and idiopathic pulmonary fibrosis. METHODS: We examined angiotensin II type 1 and 2 receptors and lymphatic vessels in the pulmonary tissues obtained from open lung biopsies of 30 patients with systemic sclerosis and 28 patients with idiopathic pulmonary fibrosis. Their histologic patterns included cellular and fibrotic non-specific interstitial pneumonia for systemic sclerosis and usual interstitial pneumonia for idiopathic pulmonary fibrosis. We used immunohistochemistry and histomorphometry to evaluate the number of cells in the alveolar septae and the vessels stained by these markers. Survival curves were also used. RESULTS: We found a significantly increased percentage of septal and vessel cells immunostained for the angiotensin type 1 and 2 receptors in the systemic sclerosis and idiopathic pulmonary fibrosis patients compared with the controls. A similar percentage of angiotensin 2 receptor positive vessel cells was observed in fibrotic non-specific interstitial pneumonia and usual interstitial pneumonia. A significantly increased percentage of lymphatic vessels was present in the usual interstitial pneumonia group compared with the non-specific interstitial pneumonia and control groups. A Cox regression analysis showed a high risk of death for the patients with usual interstitial pneumonia and a high percentage of vessel cells immunostained for the angiotensin 2 receptor in the lymphatic vessels. CONCLUSION: We concluded that angiotensin II receptor expression in the lung parenchyma can potentially control organ remodeling and fibrosis, which suggests that strategies aimed at preventing high angiotensin 2 receptor expression may be used as potential therapeutic target in patients with pulmonary systemic sclerosis and idiopathic pulmonary fibrosis.